Hadis Tentang Menikah Dengan Mahram Melalui Pendekatan Psikologi - Fadllillah, Nurul; Muhid, Muhid; Nurita, Andris (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2024)
Marriage is a very important and sacred event in life, because marriage is a step towards entering a new life. The hadith stipulates the monastery of a child to be married because of marriage. All clerics agreed on the existence of such a monasticism between breastfed children and breastfeeding women. The breastfed child becomes a child for the woman who feeds him so it is illegitimate to marry forever. For the child can look at the woman, be alone, and travel together. In this study using the type of library research (library research), this research is also qualitative. The prohibition of marriage is also sometimes necessary based on eugenic reasons (to glorify or improve race) such as the prohibition of remarriage for lunatics, severe memory weakness, people with epilepsy (ayan), and people with other severe mental illnesses. As for the meaning of the prohibition of marrying mahram, especially mahram persusuan, namely marrying a persusuan brother or persusuan mother, but in this case the marriage is prohibited because in the hadith of the Prophet is actually an illegitimate relationship equal to forbidden because of the nasab relationship, and is prohibited both by the State Law and the Islamic religion. However, if inbreeding occurs, it is feared that there will be diseases or problems that cause the personality or personality of a person, especially children, to be bad.